2006
DOI: 10.4103/0250-474x.25735
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric estimation of Betaxolol Hydrochloride in bulk powder and its dosage forms

Abstract: A simple and sensitive spectrophotometric method has been developed for determination of betaxolol hydrochloride in bulk powder, and its pharmaceutical dosage forms. In the proposed method, betaxolol is oxidized with sodium periodate, to liberate formaldehyde, which is determined in situ, using acetyl acetone in the presence of ammonium acetate. A yellow coloured chromogen was obtained having absorption maxima at 405 nm. The method is found to be linear in the concentration range of 5-30 µg/ml, with a regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Based on the literature reports on impurity identification for ETC in human plasma by HPLC-MS/MS, 9-13 HPLC, 14 and spectrophotometric. 15 Furthermore, by using UPLC-ICP-MS, ETC was found in inflammatory arthritis patients' serum and synovial fluid. 16 Robert Hartman et al, (2003) thirteen PRIs and three major DRIs were reported, 14 and S. Venugopal et al, (2011) three PRIs and DRIs also reported in ETC.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature reports on impurity identification for ETC in human plasma by HPLC-MS/MS, 9-13 HPLC, 14 and spectrophotometric. 15 Furthermore, by using UPLC-ICP-MS, ETC was found in inflammatory arthritis patients' serum and synovial fluid. 16 Robert Hartman et al, (2003) thirteen PRIs and three major DRIs were reported, 14 and S. Venugopal et al, (2011) three PRIs and DRIs also reported in ETC.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1: Molecular structures of Etoricoxib spectrophotometry18 and capillary zone electrophoresis 19. HPTLC20,21 method employing a chloroform: methanol: toluene (4:2:4 v/v) mobile phase were applied to quantify ETC in the samples.…”
mentioning
confidence: 99%